1987
DOI: 10.1017/s0081305200025450
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Local Versus Out-Of-State Grown Selected Fresh Produce: The Case of Knoxville, Tennessee

Abstract: Consumer behavior with respect to purchase regularity, satisfaction, origin, and willingness to pay for selected local versus non-Tennessee grown fresh produce is examined. Except for origin, consumer behavior with respect to the above is affected by income, household size and age distribution, race, age of respondent, college education, and occupation. The pattern of significant variables changed by commodity. Tomatoes, followed by peaches, had the greatest local market potential. Local promotion of other pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 5 publications
0
23
0
2
Order By: Relevance
“…This study uses a contingent valuation framework because this approach allows isolating consumer preferences for a specific product attribute (''SC grown'' in this case) and measuring consumer willingness to pay (WTP) for this attribute. Most previous studies have either focused on the importance of the ''local'' attribute at the specific product level (e.g., Darby et al, 2008;Eastwood et al, 1987;Loureiro & Hine, 2002), or at the aggregate agricultural product level (Brown, 2003;Jekanowski, Williams, & Schiek, 2000). This study extends the literature by calculating and comparing consumer willingness to pay for the ''local'' attribute at an intermediate level of produce and animal product aggregation.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This study uses a contingent valuation framework because this approach allows isolating consumer preferences for a specific product attribute (''SC grown'' in this case) and measuring consumer willingness to pay (WTP) for this attribute. Most previous studies have either focused on the importance of the ''local'' attribute at the specific product level (e.g., Darby et al, 2008;Eastwood et al, 1987;Loureiro & Hine, 2002), or at the aggregate agricultural product level (Brown, 2003;Jekanowski, Williams, & Schiek, 2000). This study extends the literature by calculating and comparing consumer willingness to pay for the ''local'' attribute at an intermediate level of produce and animal product aggregation.…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have shown that consumers often respond to nonpecuniary factors in their choice of consumption locally grown products (e.g., Eastwood et al, 1987;Scarpa, Phillippidis, & Spalatro, 2005). Consumer characteristics describing length of residence in the state, employment in agricultural sectors, and making purchases through direct marketing outlets are included to represent these nonpecuniary factors.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In a 1985 survey, three of the same researchers in Knoxville, Tennessee, found that among five produce items studied, only with tomatoes were consumers concerned with origin. Even for tomatoes, concern about origin was significant only among older consumers (Eastwood et al, 1987).…”
Section: Previous Studies Of Consumers and Locally Grown Producementioning
confidence: 99%
“…Consumers' preference for local food has not always been strong. Nearly two decades ago, Eastwood et al (1987) found that generally consumers were not willing to pay a significant premium for local food. Brown (2003) did not find any significant willingness to pay for local food products unless the local products possess additional characteristics compared to food from other regions.…”
Section: Research Backgroundmentioning
confidence: 99%